UNCAN.eu, the European platform to understand cancer, and childhood cancers - Gilles Vassal (EJC Paediatric Oncology)
The EU will create the UNCAN.eu platform, a European Federated Data Hub to provide access to high -quality cancer research data in order to better understand cancer and drive innovation. A Coordinated and Supported Action has delivered to the EU in November 2023 a blueprint of the UNCAN.eu including a strategic roadmap, the needed data and infrastructures, the interactions with all EU infrastructures and initiatives, a governance, a financial plan and a budget. SIOP Europe and CCI Europe were partners of the consortium to address the needs of children, adolescents and young adult with cancer as well as childhood cancer survivors. This article summarizes the blueprint proposal and how the UNCAN.eu could facilitate the implementation of a European Childhood Cancer Data Strategy through facilitated access to comprehensive childhood cancer data (molecular data, imaging, pathology, clinical trials and real world data) to accelerate innovation for children, adolescents and young adults with cancer.